The method of endogenous gridpoints for solving dynamic stochastic optimization problems - Christopher D. Carroll (The Johns Hopkins University, Department of Economics, 2005)
This paper introduces a method for solving numerical dynamic stochastic optimization problems that avoids rootfinding operations. The idea is applicable to many microeconomic and macroeconomic problems, including life cycle, buffer-stock, and stochastic growth problems. Software is provided.
Keywords: C6; D9; E2; 330; Dynamic optimization; precautionary saving; stochastic growth model; endogenous gridpoints; liquidity constraints; Stochastischer Prozess; Mathematische Optimierung; Theorie